Murder in paradise [compact disc, unabridged] : thrillers - Patterson, James, 1947-; Allyn, Douglas; Hyde, Connor; Swierczynski, Duane (Hachette Audio, 2018)
A collection of three novellas includes "The Lawyer Lifeguard," in which, after surviving a car bomb that killed his fiancée, defense lawyer Brian Lord takes a lifeguard job at the beach.